HIV-related knowledge and perceptions by academic major: Implications for university interventions - Matthew Lee Smith; Matthew Lee Smith; Lisa L La Place; Mindy eMenn; Kelly L Wilson (Frontiers Media S.A., 2014)
Most universities offer human sexuality courses, although they are not required for graduation. While students in health-related majors may receive sexuality education in formal settings, majority of college students never receive formal sexual health or HIV/AIDS-related education, which may lead to elevated engagement in high-risk sexual behaviors. This study examines perceived knowledge about HIV/AIDS, perceived risk, and perceived consequences among college students by two distinct classifications of academic majors. Data were collected from 510 college students. Binary and multinomial logistic regressions were performed to compare HIV-related covariates by academic major category. Limited differences were observed by Science, Technology, Engineering, and Mathematics (STEM) categorization. Relative to health and kinesiology (HK) majors, those who self-reported being completely knowledgeable about HIV were less likely to be physical sciences, math, engineering, business (PMEB) [OR=0.41, P=0.047] or education, humanities, and social sciences (EHS) majors [OR=0.25, P=0.004]. PMEB majors were less likely to report behavioral factors as a risk for contracting HIV [OR=0.86, P=0.004] and perceived acquiring HIV would be more detrimental to their quality of life [OR=2.14, P=0.012], but less detrimental to their mental wellbeing [OR=0.58, P=0.042]. Findings can inform college-wide campaigns and interventions to raise HIV/AIDS awareness and improve college health.